LESSON STUDY UNTUK MENINGKATKAN MUTU PROSES DAN HASIL PEMBELAJARAN PERKULIAHAN DASAR PEMISAHAN ANALITIK (Jurnal Inovasi Pendidikan Kimia, 2008)
The research of Lesson Study followed by the observation composed by analytical expertise lecturers was conducted. The aims of this activity are to raise the quality of lesson plan  produced  by  the  lecturers,  the  mastering  of  learning  material  for  each  of  lecturers conducting  the Principles  of Analytical Separation  course,  the  knowledge  of  observing the  learning  activity, and motivation  of  lecturer  for  self-developments. The responses of lecturers showed that they acquired a good comprehension, particularly on how the students learning and how lecturers teaching. The others are they got a positive value inside the learning process; they had the ability to improve the learning process systematically through collaborative inquiry and they got knowledge from the other lecturers. Thereby, the Lesson Study activity had to be experienced the benefi t by the analytical expertise lecturers. From the obtained results, it is suggested that the lesson study would be applied continually and collaboratively, so we could gain various benefi ts such as collegiality strengthening and the reinforcement of daily learning activity related to the long term purposes.Keywords: lesson study; process quality; learning result